Management of magnetic field from quadruple tower transmission lines / Ismail Said …[et al.] - Said, Ismail; Syed Jalal, Thahirah; Hussain, Halil; Abdul Rahman, Nazaruddin (2006)
Electric and magnetic fields exists whenever electricity is generated, transmitted and used. Recent worldwide attention to the harmful effects of magnetic fields emanating from power lines resulted in a growing motivation to develop methods for management of magnetic field aimed at reducing possibilities of such hazards. To optimize the usage of land, the use of quadruple tower for electric power transmission is on the increase. This paper presents the results of magnetic field simulation studies conducted on the quadruple tower transmission lines currently used in Malaysia. The results of the simulation studies were categorized to indicate the best conductor phase arrangement for lowest peal magnetic field, lowest average magnetic field and lowest magnetic field at the edge of the right-of way. It was found that magnetic field reduction of more than 90% can be achieved using proper conductor phase arrangement.